CONSTRUCTION OF THE `NATIONAL-POPULAR': COMMUNISM AND THE FOUNDING OF DEMOCRACY IN KERALA - NISSIM MANNATHUKKAREN
The state of Kerala in India is one of the most celebrated cases of social development in the world with its achievement of remarkable levels of human development despite low levels of per capita GDP. While the role of communism and mass participation in the making of the Kerala `model' of development has been studied in great detail, the processes through which communism entrenched itself in the social imaginary of a `traditional' society have hardly been explored. Against the recent scholarship that posits communism as merely addressing local concerns which had nothing to do with anti-feudalism and anti-imperialism, this paper will argue that the communist success can only be understood by its ability to fashion a Gramscian `national-popular' will which simultaneously negotiated exclusions based on class, caste, language, region and the nation. The communist (and its precursor socialist) intervention in society created wider political unities by linking the countryside and the city, the peasantry and the proletariat, class and caste. If the Indian anti-colonial struggle led by Gandhi culminated in a `passive revolution' in which the bourgeoisie gained dominance (with significant compromises with feudalism) at the expense of the laboring majority, Kerala alone among the Indian states approximated a democratic revolution with the peasantry and working class at its helm thus putting question marks on the famous dictum of Barrington Moore Jr.: "No bourgeois, no democracy." Based on archival and field research this paper will look at the period from 1930 to 1957.